2019
DOI: 10.1186/s12199-019-0795-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between metal concentrations in whole blood and placenta previa and placenta accreta: the Japan Environment and Children’s Study (JECS)

Abstract: Background Placenta previa and placenta accreta associate with high morbidity and mortality for both mothers and fetus. Metal exposure may have relationships with placenta previa and placenta accreta. This study analyzed the associations between maternal metal (cadmium [Cd], lead [Pb], mercury [Hg], selenium [Se], and manganese [Mn]) concentrations and placenta previa and placenta accreta. Methods We recruited 17,414 women with singleton pregnancies. Data from a self-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
1
16
0
2
Order By: Relevance
“…In previous literature, variable effects of Mercury on animal growth have been reported [7]. Our results are in agreement with the reports of Mehboob and coworkers, who reported a decrease in body weight in Mercury-intoxicated group [7, 39]. In the current investigation, we observed that C. album and vitamin C ameliorated mercury-induced weight loss.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In previous literature, variable effects of Mercury on animal growth have been reported [7]. Our results are in agreement with the reports of Mehboob and coworkers, who reported a decrease in body weight in Mercury-intoxicated group [7, 39]. In the current investigation, we observed that C. album and vitamin C ameliorated mercury-induced weight loss.…”
Section: Discussionsupporting
confidence: 93%
“…Approximately 2200 metric tons of mercury have been assessed to be released into the atmosphere annually [4]. Elevated levels of mercury can impair the brain, nerves, kidneys, muscles of adults, and the developing fetus [5–7]. Bronchitis, asthma, and temporary respiratory problems have been occurred due to inhalation or exposure to mercury vapors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Anderson-Bagga et al reported that prior placenta previa was a risk factor for placenta previa during subsequent pregnancies [15]. Placenta accreta and placenta previa have some common risk factors, such as disruption of the uterine endometrium, manual removal of the placenta, and uterine scarring due to intrauterine or intraoperative procedures or other gynecological surgeries [20]. Jauniaux et al reported that the complication of placenta previa was present in more than 90% of patients with placenta accreta [12,21].…”
Section: Discussionmentioning
confidence: 99%
“…The area of scarring will exhibit poor vascularization, deficient tissue oxygenation, and inflammation, which may inhibit reepithelialization and decidualization, leading to abnormal placental anchoring villi and invasion of trophoblasts [23]. Inappropriate implantation and placental development have been found during the subsequent pregnancy in women with a history of placenta previa [20]. In our study, the risk of PPH in women with a history of placenta previa was 2.25 times that in women without this history in the cesarean delivery group, but in the vaginal delivery group, a history of placenta previa did not increase the risk of PPH.…”
Section: Discussionmentioning
confidence: 99%
“…previa placenta, category, ultrasound, maternal outcome, perinatal outcome preterm delivery, or may have low birth weight or congenital defects [5].…”
Section: Introductionmentioning
confidence: 99%